Improving care and support for people with progressive illness in primary care. (1st April 2011) - Harrison, N; Cavers, D; Campbell, C; Murray, S A
Abstract : Abstract: Introduction and aims: The Palliative Care Directed Enhanced Service (DES) was introduced in Scotland in 2008/2009 to stimulate anticipatory care by GP practice teams. We aimed to evaluate how practices were implementing this by assessing how they were ▶ identifying patients for their palliative care register (PCR), ▶ assessing/reviewing needs, ▶ sharing information with out of hours (OOH) providers, ▶ using the Liverpool Care Pathway (LCP). Methods: Six practices were recruited from three Scottish Health Boards. Data were collected on current palliative care patients and on patients dying in the previous 6 months; semi-structured interviews were conducted with GPs, district nurses (DN) and administrative staff (total 20) and with patients and bereaved relatives (total 11); the researcher observed multidisciplinary practice meetings. Results: Only 29% of patients were on the PCR prior to death (range 10–38% between practices). Of these, 69% had cancer, 17% organ failure and 14% dementia or physical frailty and 25% died in hospital (cf. 44% of all deaths). 52% on the current PCR had a record of preferred place of care and 35% of resuscitation status. Practices valued better focused and structured palliative care, improved communication with OOH providers and introduction of the LCP but raised some difficulties in including non-cancer patients on the PCR. Patients and relatives appreciated pro-active care. Conclusion: Despite this initiative few patients were identified for palliative care. However when identified, their multidisciplinary and OOH care improved and hospital admissions to die decreased. Practices must identify more patients earlier for palliative care.